2012
DOI: 10.1080/00224499.2012.661489
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Online and Offline Explorations of Identity, Relationships, and Sex: A Mixed-Methods Study with LGBT Youth

Abstract: Although the Internet is commonly used by lesbian, gay, bisexual, and transgender (LGBT) youth to explore aspects of sexual health, little is known about how this usage relates to offline explorations and experiences. This study used a mixed-methods approach to investigate the interplay between online and offline explorations of multiple dimensions of sexual health, which include sexually transmitted infections, sexual identities, romantic relationships, and sexual behaviors. A diverse community sample of 32 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(189 citation statements)
references
References 35 publications
6
153
0
5
Order By: Relevance
“…Access to technology and informational resources are critical determinants in how LGBTQ young people can learn about their identity and issues related to their well-being (DeHaan, Kuper, Magee, Bigelow, & Mustanski, 2013). From this perspective, the college environment may not only be more conducive to identity development, but it can also expose college students to a wider variety of identity options from which they may choose, whereas homeless young adults may not reach that level of identity complexity as they struggle to meet their basic needs.…”
Section: Discussionmentioning
confidence: 99%
“…Access to technology and informational resources are critical determinants in how LGBTQ young people can learn about their identity and issues related to their well-being (DeHaan, Kuper, Magee, Bigelow, & Mustanski, 2013). From this perspective, the college environment may not only be more conducive to identity development, but it can also expose college students to a wider variety of identity options from which they may choose, whereas homeless young adults may not reach that level of identity complexity as they struggle to meet their basic needs.…”
Section: Discussionmentioning
confidence: 99%
“…Omdat relatie-en sekspartners van het eigen geslacht minder in hun directe omgeving te vinden zijn, is de kans aanwezig dat homo-en biseksuele jongeren deze meer dan heterojongeren via het internet vinden (De Haan, Kuper, Magee, Bigelow, & Mustanski, 2013;Pingel, Bauermeister, Johns, Eisenberg, & Leslie-Santana, 2013). In Amerikaanse onderzoeken kwam het uitwisselen van seksueel getinte beelden frequent voor onder jonge mannen die seks hebben met mannen (Bauermeister, Yeagley, Meanley & Pingel, 2014) en jonge biseksuele vrouwen (Klettke, Hallford, & Mellor, 2014).…”
Section: Hanneke De Graaf En Koenraad Vermeyunclassified
“…Daarnaast consumeren in het algemeen mannen vaker seksueel prikkelend materiaal dan vrouwen (Peter & Valkenburg, 2011;Traeen et al, 2006). Op basis van de literatuur die hierboven is beschreven, verwachten wij dat homo-en biseksuele jongeren zich vergeleken met heterojongeren in mindere mate tot ouders en vrienden wenden bij vragen of problemen over seks (Friedman & Morgan, 2009;Rose & Friedman, 2012) en dat ze meer gebruik maken van internet voor informatie, sociale steun en het zoeken van partners voor relaties en seks (De Haan et al, 2013;Mitchell et al, 2014;Pingel et al, 2013;Ybarra et al, 2015). Ook verwachten we dat homoseksuele jongens en biseksuele jongens en meisjes naar verhouding meer gebruik maken van seksueel expliciet materiaal dan heterojongeren (Rutgers WPF, 2013).…”
Section: Hanneke De Graaf En Koenraad Vermeyunclassified
See 1 more Smart Citation
“…This is particularly true for LGBT youth, who often use online communication to supplement their perceived limited offline exposure to other members of the community [3]. GLSEN et al [4] found that half of LGBT youth with less offline community participation connected with other community members online, and 14% said they had "first disclosed their LGBT identity to someone online".…”
Section: Introductionmentioning
confidence: 99%